Tanzania Economic Update : Opening the Gates - How the Port of Dar es Salaam Can Transform Tanzania - World Bank (Washington, DC, 2014)
The wide media coverage of the series as well as the interest in the blog show that the debate has been gradually moving from ministerial corridors to the public arena. This latest update foresees that the Tanzanian economy will maintain its resilience by continuing to grow at about 7 percent in the coming years. If some clouds are looming on the external and fiscal horizons, the update argues that the risks they pose should be manageable. The majority of the country s top 100 mid-size enterprises believe that 2013 will be better than 2012; and 2014 better than 2013. Nevertheless, a growing consensus today is that Tanzania needs to rely more than today on private enterprises to achieve faster and more equitable growth, as private enterprises are the ones that can provide jobs, build infrastructure, and bring new technology to the local economy. Many actions are needed on the policy front, especially to improve the business environment. Tanzania has gradually opened its economy since the early 2000s; it is also true that business coming in and going out of the country remains costly. To reduce trade costs, the priority should be to transform the Port of Dar es Salaam. An efficient port is critical because approximately 90 percent of Tanzania s international trade goes through its gates. This is a welcome development for local and regional consumers and firms that heavily depend on the performance of the port in their daily endeavors.